Without a trace [compact disc, unabridged] - Roberts, Nora (Roberts, Nora. O'Hurley collection, 2010)
Trace O'Hurley turned his back on responsibility and commitment long ago. Now he lives the way he wants, does what he wants when he wants. But that is all going to change.